(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: The Federal Supreme Court has recognized the constitutionality of confessional religious education in public schools. Excerpts from the vote of the rapporteur minister Alexandre de Moraes are representative of the majority that was formed in that Court. These passages denote that the judicial manifestation adopted as one of its premises the recognition of morality as the object of a religious teaching. Based on Osvaldo Ribeiro Luiz’s work on moral religious education, Dermeval Saviani historical-critical pedagogy and the method proposed by Edgar Morin, the model of religious teaching as moral is criticized. Also noteworthy is the incompatibility of this model with religious freedom and state secularism. This criticism takes into account the predominance in public spaces of the Christian religious tradition. Keywords: Religious education. Moral. Religious freedom.